(untitled) (Experimental biology, 2024)
The article presents the results of the study of reference sites with the medicinal plant Chelidonium majus L. in the Kazakh part of the Kungai Alatau. Descriptions of 5 reference sites with typical communities (floristic composition and structure) of different vegetation belts are given. Kungai Alatau is a peculiar and interesting region of the Northern Tien Shan, located at the junction of three botanical-geographical provinces different in their natural features: Central Tianshan-Zaalai, Kashgar-East Tianshan transitional and Dzungar transitional. The study region is of interest as a transboundary territory with the Republic of Kyrgyzstan with a high degree of botanical diversity. Due to its border physical-geographical position, the formation of its flora was influenced by different large botanical-geographical centers (Northern and Western Tien Shan). The species composition of natural complexes of many parts of the ridge has been preserved in a natural state due to its inaccessibility and represents a reference in floristic respect for the whole Northern Tien Shan. The authors of the work conducted cycles of studies on the study and distribution of C. majus on the territory of the Kazakh part of the Kungai Alatau Ridge. Kungai Alatau, which allowed now to obtain more complete data on the existence of populations of the studied species, the peculiarities of their habitat in different plant communities, the identification of the degree of impact of negative factors on the population and the duration of the consequences of the negative impact. It was found that C. majus mainly grows on mountainous southern slopes of the lower and middle belt, among bushes, along the banks of rivers and along the plumes of slopes of gorges.